The American Essay in the American Century - Stuckey-French, Ned (Book collections on Project MUSE., 2011)
"With extensive research and a cultural context, Stuckey-French describes the many reasons essays grew in appeal and importance for Americans. He also explores the rise of E.B. White, considered by many the greatest American essayist of the first half of the twentieth century ... This book is one of the first to consider and reflect on the contributions of E.B. White to the personal essay tradition and American culture more generally"--Jacket